3-D finite element modeling of sequential oblique cutting of unidirectional carbon fiber reinforced polymer. (15th January 2021) - Xu, Xiaofan; Jin, Xiaoliang
Highlights: A new 3-D micro-mechanical FE model on oblique machining of CFRP is developed. Chip formation and cutting forces in out-of-plane direction are determined. The effect of sequential cutting on surface damage is evaluated. Oblique cutting experiments were conducted to evaluate the FE model. Abstract: Machining of carbon fiber reinforced polymers (CFRP) such as milling and drilling is in the form of oblique and sequential cutting at the tool edge. The material removal mechanism and surface quality are highly dependent on the fiber orientation and oblique angle. This paper presents a 3-D finite element model of oblique cutting of unidirectional CFRP. The effects of the fiber orientation and oblique angle on the chip formation mechanism, cutting force generation, and surface damage are determined. To investigate the effect of sequential cutting, a second cut on the machined surface material is simulated. The effects of sequential cutting and random fiber distribution on the cutting forces and surface damage are analyzed. Oblique cutting experiments were conducted to evaluate the FE model by comparing the simulated and experimental cutting forces and chip morphology.